Full-Scale Full-Ring Experimental Study on Shield Tunnel Lining Structure with Innovative Segment Joints - ZHAO Mingying; HE Yingdao; WU Xinlin; ZHANG Zhaoyi; BAI Haiwen; LIU Xian (Chengshi guidao jiaotong yanjiu)
[Objective] Presently, shield tunnel structures in China face challenges including local segment weakening, significant joint deformation, low construction efficiency and hindered automated assembly. Therefore, it is necessary to study the mechanical properties of shield tunnel structures with innovative segment joints. [Method] The test overview, loading scheme and test system are introduced. Based on the mechanical properties of innovative segment joints, an analysis on the mechanical properties of shield tunnel lining structures is conducted, and a full-scale full-ring test on such structures is carried out. [Result & Conclusion] The convergence deformation, joint deformation and connector stress of the shield tunnel lining structure with innovative segment joints under various working conditions all meet design requirements; the overall segment structure deformation shows asymmetric characteristics, with both the segment structure deformation and internal force of the right waist greater than those of the left waist; the segment structure stiffness in the elastic stage is 2.21×104 N/mm. Since the stress on the connector of positive moment joints is more unfavorable than that on negative moment joints, special attention should be paid to the stress of joints at the top and bottom of the segment structure during construction and operation process.